FEW POST-LARVAL STAGES OF ANODONTOSTOMA CHACUNDA HAMILTON - Bensam, P (Indian Journal of Fisheries, 2011)
Anodontostoma chacunda, popularly called the short-nose gizzard-shad, is a fairly common fish of minor economic importance found along the coasts and estuaries of India. Information hitherto available on its early life history is limited to the observations made on the eggs and larvae by Delsman (1926 b, 1933) from the Java Sea; Devanesan and Chidambaram (1941), Chacko (1950) and Bapat (1955) from Indian coastal waters. The present paper deals with five stages in the post-larval development of this fish collected from the plankton off Cannanore (south-west coast of India) at 6 fathoms depth on 8-2-1961. The figures and measurements given are of the larvae preserved in formalin. The term ’postlarva’ is used in accordance with the definition given by Jones (1950).